2017
DOI: 10.1080/08927014.2017.1381688
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of heat and antibiotics on Pseudomonas aeruginosa biofilms

Abstract: Upon formation of a biofilm, bacteria undergo several changes that prevent eradication with antimicrobials alone. Due to this resistance, the standard of care for infected medical implants is explantation of the infected implant and surrounding tissue, followed by eventual reimplantation of a replacement device. Recent studies have demonstrated the efficacy of heat shock for biofilm eradication. To minimize the heat required for in situ biofilm eradication, this study investigated the hypothesis that antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…The observed synergistic effect between heat and antibiotics (without NAC) is in accordance with Hajdu et al, who have shown enhancement of antibacterial activity of antimicrobial agents against staphylococcal biofilms by increasing the ambient temperature [15]. Ricker and Nuxoll have also demonstrated this synergistic effect of antibiotics and heat in a Pseudomonas film for erythromycin, tobramycin, and ciprofloxacin [28]. Both Hajdu and Ricker and Nuxoll used heat conduction rather than induction heating [15,28].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The observed synergistic effect between heat and antibiotics (without NAC) is in accordance with Hajdu et al, who have shown enhancement of antibacterial activity of antimicrobial agents against staphylococcal biofilms by increasing the ambient temperature [15]. Ricker and Nuxoll have also demonstrated this synergistic effect of antibiotics and heat in a Pseudomonas film for erythromycin, tobramycin, and ciprofloxacin [28]. Both Hajdu and Ricker and Nuxoll used heat conduction rather than induction heating [15,28].…”
Section: Discussionsupporting
confidence: 84%
“…Ricker and Nuxoll have also demonstrated this synergistic effect of antibiotics and heat in a Pseudomonas film for erythromycin, tobramycin, and ciprofloxacin [28]. Both Hajdu and Ricker and Nuxoll used heat conduction rather than induction heating [15,28].…”
Section: Discussionmentioning
confidence: 98%
“…The effect of heat shock on the susceptibility of bacterial biofilms to antibiotics has been studied in experimental systems that induce uniformly increased temperature to culture media [6,13]. For example, the application of heat shock at a DT of 13 C for 30 min or a DT of 23 C for 5 min exhibited synergistic effects in eradicating P. aeruginosa biofilm when combined with antibiotics including ciprofloxacin or tobramycin [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the application of heat shock to the biofilm phase of bacteria by means of uniformly increasing temperature in the culture media could significantly enhance the susceptibility of Staphylococcal as well as Pseudomonas aeruginosa (P. aeruginosa) biofilm to conventional antibiotics [13,14]. Furthermore, the application of AMF on P. aeruginosa biofilm formed on metallic implants rendered the bacteria more susceptible to antibiotics via heat-mediated removal of the biofilm extracellular polymeric substances (EPS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the emergence of antibiotic resistance around the globe, many alternative strategies have been developed to eradicate biofilm formation, including physical (heat and ultrasound) (Cai et al, 2017;Ricker and Nuxoll, 2017;Wang et al, 2018), chemical (organic acids) (Ryssel et al, 2009;Ban et al, 2012;Singla et al, 2014) and biological (bacteriophage) (Tkhilaishvili et al, 2018;Gupta et al, 2019) methods. However, there are some limitations to existing treatment methods.…”
mentioning
confidence: 99%